2008
DOI: 10.1002/bit.21905
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening of chromatographic separations: IV. Ion‐exchange

Abstract: Ion-exchange (IEX) chromatography steps are widely applied in protein purification processes because of their high capacity, selectivity, robust operation, and well-understood principles. Optimization of IEX steps typically involves resin screening and selection of the pH and counterion concentrations of the load, wash, and elution steps. Time and material constraints associated with operating laboratory columns often preclude evaluating more than 20-50 conditions during early stages of process development. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 25 publications
3
66
0
Order By: Relevance
“…1B). A similar relationship has also been noted for AEX resins (Kelley et al, 2008a). Because of this strong correlation between K p and Q 70 , HTS data from the low challenge region and the resulting correlations can be used to predict product binding well in the non-linear region, which would be valuable for cycle development.…”
Section: Binding Htssupporting
confidence: 64%
“…1B). A similar relationship has also been noted for AEX resins (Kelley et al, 2008a). Because of this strong correlation between K p and Q 70 , HTS data from the low challenge region and the resulting correlations can be used to predict product binding well in the non-linear region, which would be valuable for cycle development.…”
Section: Binding Htssupporting
confidence: 64%
“…76 Agreement with results obtained by chromatographic methods is generally good. Kelley et al demonstrated optimization of a cation exchange capture step for a recombinant human mAb carried out in 8 hrs using 35 mg of protein in total; they evaluated eight different resins and multiple pH and salt conditions for binding and elution.…”
Section: Chromatographic Processesmentioning
confidence: 70%
“…Kelley et al demonstrated optimization of a cation exchange capture step for a recombinant human mAb carried out in 8 hrs using 35 mg of protein in total; they evaluated eight different resins and multiple pH and salt conditions for binding and elution. 76 Their results clearly demonstrate the potential for rapid screening of initial operating conditions that can be subsequently defined by conventional packed bed chromatography.…”
Section: Chromatographic Processesmentioning
confidence: 82%
“…Since the completion of this study, high-throughput screens have successfully encompassed up to eight sequential elution stages per well (Kelley et al, 2008a). A single-well design is superior to the split-gradient design because twice as many conditions can be explored in a single filterplate, half the protein is required, and the split-gradient design may have caused artifacts in the resulting chromatograms.…”
Section: Hic Resin Screenmentioning
confidence: 98%